EFFECTIVENESS OF EDITING IN PREPARATION OF ORIGINAL ARTICLES: RESULTS OF RANDOMIZED CONTROLLED STUDY - R.T. Saygitov ("Paediatrician" Publishers LLC, 2010)
The data on effectiveness of editing in medical journals is restricted. Objective: to study an effectiveness of editing in improvement of manuscripts quality containing results of original study, which were published in the journal «Current Pediatrics» (Russia). Design: single blinded randomized controlled study in parallel groups. Consecutive eligible papers were sent to reviewers (n=137) who were randomised into 2 groups (1:1) for evaluation of five author's or edited (accepted for publication) manuscripts. Main outcome measures: item of importance, originality, methods, data presentation, discussions and conclusion quality score were evaluated. Results: 102 (74%) participants gave at least one conclusion, 64 (47%) performed an estimation of all presented materials. 412 conclusions (208 on author's manuscripts and 204 on edited ones) were analyzed. An analysis showed equal estimation of importance, methods, discussions and conclusions in both author's and edited manuscripts. Evaluation of data presentation quality was higher in edited materials: odds ratio (OR) for estimation ≥ 3 according 5-point scale was 4.1 (95% CI 2.0-8.4) times higher than in author's manuscripts. Higher estimation of editing effectiveness was received from «strict» readers (mean estimations of manuscripts quality in lower quartile). They mentioned that editing improves quality of data presentation - for estimation ≥ 3 according to 5-point scale OR was 7.8 (95% CI 2.9-20.6), conclusions - OR 2.3 (95% CI 1.0-5.2), methods - OR 2.2 (0.9-5.3; p = 0.068), and makes common impression of edited manuscripts better as well. Conclusion: editing improves quality of data presentation and description of conclusions and methods («strict» readers only) in manuscripts of original study.Key words: reviewing, editing, original articles, quality.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):5-15)